Film

A film composition of poly(3-hydroxyalkanoate) and polylactic acid resins addresses the slow crystallization and contamination issues of poly(3-hydroxyalkanoate) resins, enabling high productivity and stable film production with enhanced biodegradability and strength.

JP2025001852APending Publication Date: 2025-01-09KANEKA CORP

Patent Information

Application Number
JP2023101568
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-21
Publication Date
2025-01-09

AI Technical Summary

Technical Problem

Poly(3-hydroxyalkanoate) resins crystallize slowly, leading to reduced processing productivity and equipment contamination due to the use of crystal nucleating agents like pentaerythritol during film production.

Method used

A film composition comprising poly(3-hydroxyalkanoate) resin and polylactic acid resin without sugar alcohols, with a specific weight ratio, to enhance productivity and prevent equipment contamination.

Benefits of technology

The film can be produced with good productivity and stability, maintaining biodegradability while avoiding equipment contamination, and achieving high stretching ratios and film strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025001852000001
    Figure 2025001852000001
Patent Text Reader

Abstract

To provide a poly(3-hydroxyalkanoate)-based resin-containing film which can be produced with good productivity while avoiding contamination of a production device.SOLUTION: A film contains a poly(3-hydroxyalkanoate)-based resin (A), and a polylactic acid-based resin (B), and does not substantially contain sugar alcohol, wherein a mass ratio (A / B) of the poly(3-hydroxyalkanoate)-based resin (A) to the polylactic acid-based resin (B) is 85 / 15 to 55 / 45. The resin (A) contains a copolymer (A-1) of a 3-hydroxybutyrate unit having a content ratio of other hydroxyalkanoate units of 24 mol% or more and the other hydroxyalkanoate units, and a copolymer (A-2) having a 3-hydroxybutyrate unit having a content ratio of other hydroxyalkanoate units of 1 mol% or more and 9 mol% or less and other hydroxyalkanoate units.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a film containing a poly(3-hydroxyalkanoate) resin. [Background technology]

[0002] In recent years, the separation and collection of food waste and composting have been promoted mainly in Europe, and there is a demand for plastic products that can be composted together with food waste. In addition, there are hopes for marine degradable plastics to solve the problem of marine pollution caused by plastics.

[0003] As a material having such compost-degradability and marine-degradability, poly(3-hydroxyalkanoate) resins, such as poly(3-hydroxybutyrate-co-3-hydroxyhexanoate), have attracted attention.

[0004] However, poly(3-hydroxyalkanoate) resins are materials that crystallize slowly compared to general thermoplastic resins, and require a long time to solidify after being heated and melted, which poses a problem of impairing the productivity of molding processes such as film molding, etc. To solve this problem, a technique is known in which a sugar alcohol such as pentaerythritol is blended as a crystal nucleating agent with a poly(3-hydroxyalkanoate) resin (see Patent Documents 1 and 2). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2014 / 020838 [Patent Document 1] International Publication No. 2008 / 099586 Summary of the Invention [Problem to be solved by the invention]

[0006] According to the methods described in Patent Documents 1 and 2, the solidification property of poly(3-hydroxyalkanoate) resin can be improved, and the productivity of molded articles containing the resin can be improved. Among them, pentaerythritol is excellent in improving the productivity, and is widely used for poly(3-hydroxyalkanoate) resin.

[0007] Therefore, the inventors continuously produced a resin film containing a poly(3-hydroxyalkanoate) resin by melting a resin raw material containing a poly(3-hydroxyalkanoate) resin and pentaerythritol in an extruder and extruding the molten resin raw material from a T-die onto a casting roll to form it into a film.

[0008] However, it was discovered that continuous production could cause some substances to adhere to the surface of the casting roll, which could have a negative impact on the manufacturing environment and film quality.

[0009] The cause of this roll contamination problem is believed to be pentaerythritol bleeding out from the molten resin raw material and adhering to the cast roll. In order to avoid this roll contamination problem, it is desirable not to use pentaerythritol. However, a formulation that does not contain pentaerythritol reduces the productivity of poly(3-hydroxyalkanoate)-based resin-containing films.

[0010] In view of the above-mentioned current situation, an object of the present invention is to provide a poly(3-hydroxyalkanoate) resin-containing film that can be produced with good productivity while avoiding contamination of the production equipment. [Means for solving the problem]

[0011] As a result of intensive research aimed at solving the above problems, the inventors discovered that by blending a specific amount of polylactic acid resin with a poly(3-hydroxyalkanoate) resin to form a film without using sugar alcohols such as pentaerythritol, which serve as crystal nucleating agents, it is possible to maintain good productivity while avoiding contamination of the manufacturing equipment, and thus completed the present invention.

[0012] That is, the present invention relates to a composition which contains a poly(3-hydroxyalkanoate)-based resin (A) and a polylactic acid-based resin (B), is substantially free of sugar alcohols, and has a weight ratio (A / B) of the poly(3-hydroxyalkanoate)-based resin (A) to the polylactic acid-based resin (B) of 85 / 15 to 55 / 45. The present invention also relates to a laminate comprising the above film and a layer containing a poly(3-hydroxyalkanoate) resin (C) laminated on at least one surface of the film. Effect of the Invention

[0013] According to the present invention, it is possible to provide a poly(3-hydroxyalkanoate) resin-containing film that can be produced with good productivity while avoiding contamination of the production equipment. According to the present invention, a resin film having good biodegradability can be provided. According to a preferred embodiment of the present invention, a poly(3-hydroxyalkanoate)-based resin-containing film having good stretchability can be provided. Therefore, even under conditions unfavorable for stretching the poly(3-hydroxyalkanoate)-based resin-containing film, the film can be stretched. In addition, the film can be stretched continuously and stably. Furthermore, a high stretching ratio can be realized. According to a preferred embodiment of the present invention, a uniaxially stretched film stretched in the MD direction or a biaxially stretched film stretched in both the MD direction and the TD direction can be produced, and a high stretch ratio can be achieved in each direction. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Hereinafter, an embodiment of the present invention will be described, however, the present invention is not limited to the following embodiment. The present embodiment relates to a film containing a poly(3-hydroxyalkanoate)-based resin (A) and a polylactic acid-based resin (B).

[0015] [Poly(3-hydroxyalkanoate) resin (A)] The poly(3-hydroxyalkanoate) resin (A) may be a single poly(3-hydroxyalkanoate) resin or a mixture of two or more poly(3-hydroxyalkanoate) resins. However, a mixture of at least two poly(3-hydroxyalkanoate) resins having different types of constituent monomers and / or different content ratios of the constituent monomers is preferred, since this makes it easier to achieve both film strength and productivity and also improves the stretchability of the film.

[0016] The poly(3-hydroxyalkanoate) resin (A) is preferably a polymer having a 3-hydroxyalkanoate unit, specifically a polymer containing a unit represented by the following general formula (1). [-CHR-CH2-CO-O-] (1)

[0017] In the general formula (1), R is C p H 2p+1 where p is an integer of 1 to 15. Examples of R include linear or branched alkyl groups such as methyl, ethyl, propyl, methylpropyl, butyl, isobutyl, t-butyl, pentyl, and hexyl. p is preferably 1 to 10, and more preferably 1 to 8.

[0018] As the poly(3-hydroxyalkanoate)-based resin (A), a poly(3-hydroxyalkanoate)-based resin produced from a microorganism is particularly preferred. In the poly(3-hydroxyalkanoate)-based resin produced from a microorganism, all of the 3-hydroxyalkanoate units are contained as (R)-3-hydroxyalkanoate units.

[0019] The poly(3-hydroxyalkanoate) resin (A) preferably contains 3-hydroxyalkanoate units (particularly units represented by general formula (1)) in an amount of 50 mol % or more, more preferably 60 mol % or more, and even more preferably 70 mol % or more of the total constituent units. The poly(3-hydroxyalkanoate) resin (A) may contain only one or more kinds of 3-hydroxyalkanoate units as the constituent units of the polymer, or may contain other units (e.g., 4-hydroxyalkanoate units, etc.) in addition to one or more kinds of 3-hydroxyalkanoate units.

[0020] The poly(3-hydroxyalkanoate) resin (A) is preferably a homopolymer or copolymer containing 3-hydroxybutyrate (hereinafter sometimes referred to as 3HB) units (hereinafter, both polymers are collectively referred to as "poly(3-hydroxybutyrate) resin"). In particular, it is preferable that all of the 3-hydroxybutyrate units are (R)-3-hydroxybutyrate units. In addition, the poly(3-hydroxyalkanoate) resin (A) preferably contains a copolymer of 3-hydroxybutyrate units and other hydroxyalkanoate units.

[0021] Specific examples of poly(3-hydroxybutyrate)-based resins include poly(3-hydroxybutyrate), poly(3-hydroxybutyrate-co-3-hydroxypropionate), poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (abbreviation: P3HB3HV), poly(3-hydroxybutyrate-co-3-hydroxyvalerate-3-hydroxyhexanoate), poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (abbreviation: P3HB3HH), Examples of such poly(3-hydroxybutyrate-co-3-hydroxyheptanoate), poly(3-hydroxybutyrate-co-3-hydroxyoctanoate), poly(3-hydroxybutyrate-co-3-hydroxynonanoate), poly(3-hydroxybutyrate-co-3-hydroxydecanoate), poly(3-hydroxybutyrate-co-3-hydroxyundecanoate), poly(3-hydroxybutyrate-co-4-hydroxybutyrate) (abbreviation: P3HB4HB), etc. In particular, from the viewpoint of film productivity and mechanical properties, etc., poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) or poly(3-hydroxybutyrate-co-4-hydroxybutyrate) is preferred.

[0022] Poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) is particularly preferred from the viewpoints that by changing the composition ratio of the repeating units, it is possible to change the melting point, the degree of crystallinity, and physical properties such as Young's modulus and heat resistance, and it is possible to impart physical properties between polypropylene and polyethylene, and that it is easy to produce industrially and is a physically useful plastic. In particular, among poly(3-hydroxybutyrate)-based resins that have the property of being easily thermally decomposed when heated at 180° C. or higher, poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) is preferred from the viewpoints that it is possible to lower the melting point and perform molding processing at low temperatures.

[0023] Commercially available products of poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) include "Kaneka Biodegradable Polymer Green Planet" (registered trademark) manufactured by Kaneka Corporation.

[0024] When the poly(3-hydroxyalkanoate) resin (A) contains a copolymer of 3-hydroxybutyrate units and other hydroxyalkanoate units, the average content ratio of 3-hydroxybutyrate units and other hydroxyalkanoate units in all monomer units constituting the poly(3-hydroxyalkanoate) resin (A) is preferably 3-hydroxybutyrate units / other hydroxyalkanoates=99 / 1 to 80 / 20 (mol % / mol %), more preferably 97 / 3 to 82 / 18 (mol % / mol %), and even more preferably 95 / 5 to 85 / 15 (mol % / mol %), from the viewpoint of achieving both film strength and productivity.

[0025] The average content ratio of each monomer unit in all monomer units constituting the poly(3-hydroxyalkanoate) resin (A) can be determined by a method known to those skilled in the art, for example, the method described in paragraph

[0047] of International Publication No. 2013 / 147139. The average content ratio means the molar ratio of each monomer unit in all monomer units constituting the poly(3-hydroxyalkanoate) resin (A), and when the poly(3-hydroxyalkanoate) resin (A) is a mixture of two or more poly(3-hydroxyalkanoate) resins, it means the molar ratio of each monomer unit contained in the entire mixture.

[0026] As described above, the poly(3-hydroxyalkanoate) resin (A) may be a mixture of at least two poly(3-hydroxyalkanoate) resins having different types of constituent monomers and / or different content ratios of the constituent monomers. In this case, at least one highly crystalline poly(3-hydroxyalkanoate) resin and at least one lowly crystalline poly(3-hydroxyalkanoate) resin may be used in combination.

[0027] In general, highly crystalline poly(3-hydroxyalkanoate) resins have excellent productivity but poor mechanical strength, while low-crystalline poly(3-hydroxyalkanoate) resins have poor productivity but excellent mechanical properties. By using both resins in combination, the strength and productivity of the film can be further improved.

[0028] The content of 3-hydroxybutyrate units in the highly crystalline poly(3-hydroxyalkanoate) resin is preferably higher than the average content of 3-hydroxybutyrate units in all monomer units constituting the poly(3-hydroxyalkanoate) resin (A). On the other hand, the content of 3-hydroxybutyrate units in the low-crystalline poly(3-hydroxyalkanoate) resin is preferably lower than the average content of 3-hydroxybutyrate units in all monomer units constituting the poly(3-hydroxyalkanoate) resin (A).

[0029] When the poly(3-hydroxyalkanoate) resin (A) is a mixture of at least two kinds of poly(3-hydroxyalkanoate) resins, the resin (A) specifically preferably contains the following copolymer (A-1) and copolymer (A-2). According to this embodiment, it is easy to achieve both the strength and productivity of the film, and the stretchability of the film can also be improved. Copolymer (A-1): A copolymer of 3-hydroxybutyrate units and other hydroxyalkanoate units, the content of which is 24 mol % or more. Copolymer (A-2): A copolymer of 3-hydroxybutyrate units and other hydroxyalkanoate units, the content of which is 1 mol% or more and 9 mol% or less.

[0030] In the copolymer (A-1), the content of the other hydroxyalkanoate units is preferably from 24 to 99 mol %, more preferably from 24 to 50 mol %, further preferably from 24 to 35 mol %, and particularly preferably from 24 to 30 mol %. In the copolymer (A-2), the content of the other hydroxyalkanoate units is preferably from 2 to 8 mol %, more preferably from 2 to 7 mol %.

[0031] As the copolymer (A-1) and the copolymer (A-2), poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) or poly(3-hydroxybutyrate-co-4-hydroxybutyrate) is preferable, and poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) is particularly preferable.

[0032] In the film according to the present embodiment, the content of the copolymer (A-1) is preferably more than 0% by weight and less than 30% by weight based on the total weight of the poly(3-hydroxyalkanoate) resin (A) and the polylactic acid resin (B) from the viewpoint of productivity and stretchability of the film. The upper limit is preferably 28% by weight or less, more preferably 25% by weight or less, and particularly preferably 22% by weight or less, from the viewpoint of productivity of the film. The lower limit is preferably 5% by weight or more, more preferably 10% by weight or more, and even more preferably 15% by weight or more, from the viewpoint of stretchability of the film. However, there may be an embodiment in which the copolymer (A-1) is not contained.

[0033] Moreover, from the viewpoint of productivity and stretchability of the film, the content of the copolymer (A-2) is preferably more than 0% by weight and less than 70% by weight based on the total weight of the poly(3-hydroxyalkanoate)-based resin (A) and the polylactic acid-based resin (B). From the viewpoint of productivity and stretchability of the film, the upper limit is preferably less than 68% by weight, and more preferably less than 65% by weight. From the viewpoint of productivity of the film, the lower limit is preferably 10% by weight or more, more preferably 20% by weight or more, even more preferably 30% by weight or more, and particularly preferably 40% by weight or more.

[0034] When the resin (A) contains the copolymer (A-1) and the copolymer (A-2), the weight ratio (A-1 / A-2) of the copolymer (A-1) to the copolymer (A-2) is preferably from 5 / 95 to 50 / 50, more preferably from 10 / 90 to 40 / 60, further preferably from 15 / 85 to 30 / 70, and particularly preferably from 20 / 80 to 30 / 70, from the viewpoints of achieving both the strength and productivity of the film and further increasing the stretchability.

[0035] The copolymer (A-2) may be a mixture of at least two kinds of copolymers having different content ratios of constituent monomers. Specifically, it is preferable to contain the following copolymer (A-2-1) and the following copolymer (A-2-2). According to this embodiment, it becomes easier to achieve both strength and productivity of the film, and the stretchability of the film can be further improved. Copolymer (A-2-1): A copolymer of 3-hydroxybutyrate units and other hydroxyalkanoate units, the content of which is 1 mol% or more and less than 4 mol%. Copolymer (A-2-2): A copolymer of 3-hydroxybutyrate units and other hydroxyalkanoate units, the content of which is 4 mol% or more and 9 mol% or less.

[0036] In the copolymer (A-2-1), the content of the other hydroxyalkanoate units is preferably from 1 to 3 mol %, more preferably from 2 to 3 mol %. In the copolymer (A-2-2), the content of the other hydroxyalkanoate units is preferably from 5 to 8 mol %, more preferably from 6 to 7 mol %.

[0037] As the copolymers (A-2-1) and (A-2-2), poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) or poly(3-hydroxybutyrate-co-4-hydroxybutyrate) is preferable, and poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) is particularly preferable.

[0038] When the resin (A) contains the copolymer (A-2-2), the weight proportion of the copolymer (A-2-2) in the entire resin (A) is preferably from 10 to 90% by weight, more preferably from 20 to 70% by weight, even more preferably from 25 to 60% by weight, and particularly preferably from 30 to 50% by weight, from the viewpoint of improving the strength, productivity, or stretchability of the film.

[0039] The method for obtaining a blend of two or more poly(3-hydroxyalkanoate) resins is not particularly limited, and may be a method for obtaining a blend by microbial production or a method for obtaining a blend by chemical synthesis. In addition, a blend may be obtained by melt-kneading two or more resins using an extruder, kneader, Banbury mixer, roll, etc., or by dissolving two or more resins in a solvent, mixing, and drying.

[0040] Resin (A) may be composed of only one type of poly(3-hydroxyalkanoate) resin. In this case, resin (A) is preferably composed of only copolymer (A-2), and more preferably composed of only copolymer (A-2-2).

[0041] The weight average molecular weight of the entire poly(3-hydroxyalkanoate) resin (A) is not particularly limited, but from the viewpoint of film strength and productivity, it is preferably from 200,000 to 2,000,000, more preferably from 300,000 to 1,500,000, and even more preferably from 400,000 to 1,000,000.

[0042] In addition, when the poly(3-hydroxyalkanoate) resin (A) is a mixture of two or more poly(3-hydroxyalkanoate) resins, the weight average molecular weight of each poly(3-hydroxyalkanoate) resin constituting the mixture is not particularly limited. However, the weight average molecular weight of the copolymer (A-1) is preferably 200,000 to 1,000,000, more preferably 220,000 to 800,000, and even more preferably 250,000 to 600,000 from the viewpoint of film strength and productivity. On the other hand, the weight average molecular weight of the copolymer (A-2) is preferably 200,000 to 2,500,000, more preferably 250,000 to 2,300,000, and even more preferably 300,000 to 2,000,000 from the viewpoint of film strength and productivity. In addition, the weight average molecular weight of the copolymer (A-2-2) is preferably 200,000 to 2,500,000, more preferably 250,000 to 2,300,000, and even more preferably 300,000 to 2,000,000 from the viewpoint of film strength and productivity.

[0043] The weight average molecular weight of the poly(3-hydroxyalkanoate) resin can be measured in terms of polystyrene using gel permeation chromatography (HPLC GPC system manufactured by Shimadzu Corporation) using a chloroform solution. As the column for the gel permeation chromatography, a column suitable for measuring the weight average molecular weight may be used.

[0044] The method for producing the poly(3-hydroxyalkanoate) resin is not particularly limited, and may be a production method by chemical synthesis or a production method using a microorganism. Among them, a production method using a microorganism is preferable. A known method can be applied to the production method using a microorganism. For example, Aeromonas caviae, which produces P3HB3HV and P3HB3HH, and Alcaligenes eutrophus, which produces P3HB4HB, are known as bacteria that produce copolymers of 3-hydroxybutyrate and other hydroxyalkanoates. In particular, with regard to P3HB3HH, in order to increase the productivity of P3HB3HH, it is more preferable to use Alcaligenes eutrophus AC32 (FERM BP-6038) (T. Fukui, Y. Doi, J. Bateriol., 179, pp. 4821-4830 (1997)) or the like, into which genes of P3HA synthase group have been introduced, and microbial cells in which P3HB3HH has been accumulated in the cells by culturing these microorganisms under appropriate conditions are used. In addition to the above, genetically modified microorganisms into which various poly(3-hydroxyalkanoate) resin synthesis-related genes have been introduced may be used according to the poly(3-hydroxyalkanoate) resin to be produced, or the culture conditions, including the type of substrate, may be optimized.

[0045] As the poly(3-hydroxyalkanoate) resin (A), an unmodified poly(3-hydroxyalkanoate) resin can be used. However, a resin obtained by modifying an unmodified poly(3-hydroxyalkanoate) resin with a raw material that reacts with the resin, such as a peroxide (hereinafter referred to as a "modifying raw material"), may also be used.

[0046] The raw material for modification is not particularly limited as long as it is a compound that can react with the poly(3-hydroxyalkanoate) resin, but an organic peroxide is preferably used in terms of ease of handling and ease of controlling the reaction with the poly(3-hydroxyalkanoate) resin. Any known compound may be used as the organic compound.

[0047] [Polylactic acid resin (B)] Polylactic acid resin (B) is a polyester with lactic acid as a constituent monomer. The glass transition temperature of poly(3-hydroxyalkanoate) resin is around 0°C, whereas that of polylactic acid resin is usually around 60°C. Therefore, when polylactic acid resin (B) is blended, the polylactic acid resin solidifies below the glass transition temperature when the molten film material is cooled on a cast roll cooled to below 60°C, which makes it less likely to stick to the cast roll, and increases the productivity of poly(3-hydroxyalkanoate) resin-containing films. It is difficult to cool the molten resin below the glass transition temperature of poly(3-hydroxyalkanoate) resin, 0°C, and maintain the state below 0°C in a practical process.

[0048] In addition, polylactic acid resins usually have a glass transition temperature of around 60°C, and are difficult to crystallize when rapidly cooled from a molten state, becoming amorphous. Therefore, by blending polylactic acid resin (B), the film is likely to soften even at a relatively low temperature of over 60°C. Therefore, by blending polylactic acid resin (B), the stretchability of the poly(3-hydroxyalkanoate) resin-containing film can also be improved. This makes it possible to obtain a high-quality stretched film without breakage during stretching and without uneven stretching. In addition, the film can be stretched continuously and stably. Furthermore, a high stretching ratio can also be achieved.

[0049] The polylactic acid resin (B) is preferably a homopolymer of lactic acid, but may contain, in addition to lactic acid, trace amounts of other monomers.

[0050] The lactic acid constituting the polylactic acid resin (B) may be either the L-form or the D-form, or may contain both. In the latter case, the ratio of the L-form to the D-form is not particularly limited. The polylactic acid resin (B) may be any one of poly(L-lactic acid) resin, poly(D-lactic acid) resin, and poly(DL-lactic acid) resin, or may be a blend of these.

[0051] Examples of the other monomers that may be contained in the polylactic acid resin (B) include aliphatic hydroxycarboxylic acids other than lactic acid, aliphatic polyhydric alcohols, aliphatic polycarboxylic acids, and polyfunctional polysaccharides. When the polylactic acid resin (B) is a copolymer of lactic acid and other monomers, from the viewpoint of crystallinity, the content of the other monomers is preferably about 0 to 3 mol %, more preferably 0 to 2 mol %, based on the total monomers contained in the polylactic acid resin (B).

[0052] The polylactic acid resin (B) may be either a crystalline polylactic acid resin or an amorphous polylactic acid resin, but it is preferable to use a crystalline polylactic acid resin from the viewpoint of heat resistance such as shrinkage during heating in subsequent processes such as printing and deposition. Among the crystalline polylactic acid resins, a polylactic acid resin having a melting point peak of less than 170° C. in differential scanning calorimetry is particularly preferable.

[0053] The peak temperature of the melting point peak of the polylactic acid resin (B) (hereinafter also referred to as "peak melting point temperature") is preferably 165° C. or lower, more preferably 160° C. or lower, from the viewpoint of improving the productivity, stretchability, and strength of the film. Moreover, the lower limit of the peak temperature is preferably 120° C. or higher, more preferably 130° C. or higher, and even more preferably 140° C. or higher, from the viewpoint of improving the productivity and stretchability of the film.

[0054] The melting peak temperature refers to the peak top temperature Tm of the crystal melting peak in a DSC curve obtained by differential scanning calorimetry (DSC measurement). The DSC curve was obtained by precisely weighing about 5 mg of the resin to be measured and heating it from 0°C to 200°C at a heating rate of 10°C / min using a differential scanning calorimeter.

[0055] The polylactic acid resin (B) exhibiting the above-mentioned melting point peak temperature is not particularly limited, and commercially available products can be used. A specific example is a polylactic acid resin having an L-isomer purity of lactic acid units of 88% or more and 98% or less.

[0056] From the viewpoint of improving the productivity and stretchability of the film, the melting peak temperature of the polylactic acid resin (B) is preferably close to the melting peak temperature of the poly(3-hydroxyalkanoate) resin (A). Specifically, the absolute value of the difference between the melting peak temperature of the polylactic acid resin (B) and the melting peak temperature of the poly(3-hydroxyalkanoate) resin (A) is preferably 40° C. or less, more preferably 30° C. or less, and even more preferably 20° C. or less.

[0057] The melting peak temperature of the poly(3-hydroxyalkanoate) resin (A) is measured in the same manner as the melting peak temperature of the polylactic acid resin (B). When multiple melting peaks appear in the DSC curve measured for the poly(3-hydroxyalkanoate) resin (A), the peak temperature of the melting peak on the high temperature side is regarded as the melting peak temperature of the poly(3-hydroxyalkanoate) resin (A).

[0058] The molecular weight of the polylactic acid resin (B) is not particularly limited and may be set appropriately, but the number average molecular weight is preferably from 1,000 to 700,000, and more preferably from 10,000 to 300,000.

[0059] The lactic acid raw material for producing the polylactic acid resin (B) is not particularly limited, and can be L-lactic acid, D-lactic acid, DL-lactic acid, or a mixture thereof, or L-lactide, D-lactide, meso-lactide, or a mixture thereof, etc. Lactic acid obtained by microbial fermentation from renewable raw materials derived from plants such as starch can be suitably used. The method for producing the polylactic acid resin (B) is not particularly limited, and any known method such as a dehydration condensation polymerization method or a ring-opening polymerization method can be used.

[0060] In the film according to the present embodiment, the poly(3-hydroxyalkanoate)-based resin (A) and the polylactic acid-based resin (B) are used in a weight ratio (A / B) of the two resins in the range of 85 / 15 to 55 / 45. By using both resins in such a weight ratio, the productivity of the poly(3-hydroxyalkanoate)-based resin-containing film can be improved by suppressing adhesion of the molten film material to a cast roll, despite the fact that the film is substantially free of sugar alcohols that function as crystal nucleating agents, and furthermore, the biodegradability of the film (particularly biodegradability in compost and marine degradability) can be improved.

[0061] From the viewpoint of improving the productivity of the film, the content of the polylactic acid resin (B) is preferably as high as possible, and therefore the weight ratio is preferably 90 / 20 to 55 / 45. On the other hand, from the viewpoint of enhancing the biodegradability of the film, the content of the polylactic acid resin (B) is preferably small, and therefore the weight ratio is preferably 85 / 15 to 65 / 35, more preferably 85 / 15 to 70 / 30, and even more preferably 85 / 15 to 75 / 25.

[0062] The film according to this embodiment is a resin film mainly composed of a poly(3-hydroxyalkanoate)-based resin (A) and a polylactic acid-based resin (B). The total proportion of the poly(3-hydroxyalkanoate)-based resin (A) and the polylactic acid-based resin (B) in the total amount of the film may be 50% by weight or more, preferably 70% by weight or more, more preferably 80% by weight or more, and even more preferably 90% by weight or more. It may be 95% by weight or more, or 98% by weight or more.

[0063] (Sugar alcohols) The film according to the present embodiment is substantially free of sugar alcohols, which are known to function as crystal nucleating agents for poly(3-hydroxyalkanoate) resins, and thus can avoid the problem of sugar alcohols bleeding out of the molten film material and contaminating the surface of the manufacturing equipment (e.g., the surface of a casting roll) that the film material comes into contact with.

[0064] Although the film of this embodiment is substantially free of sugar alcohols, the incorporation of a specific amount of polylactic acid-based resin (B) promotes solidification of the molten film material, enabling the poly(3-hydroxyalkanoate)-based resin-containing film to be produced with good productivity.

[0065] The sugar alcohol may be a compound known as a crystal nucleating agent for poly(3-hydroxyalkanoate) resin.Specific examples thereof include pentaerythritol, erythritol, D-arabitol, ribitol, xylitol, galactitol, D-mannitol, L-mannitol, D-sorbitol, myo-inositol, scyllo-inositol, maltitol, lactitol, and the like.Among these, it is preferable that the sugar alcohol does not substantially contain pentaerythritol.

[0066] "Substantially free of sugar alcohols" means that the sugar alcohols are blended in an amount that is not recognized to function as a crystal nucleating agent for the resin component of the film, or that the amount is zero. Specific values ​​for the amount of sugar alcohols blended include, for example, an amount of 0 parts by weight or more and less than 0.1 parts by weight per 100 parts by weight of the total of the poly(3-hydroxyalkanoate) resin (A) and the polylactic acid resin (B). It may be less than 0.01 parts by weight. It is most preferable that the amount of sugar alcohols blended is zero.

[0067] (Other resins) The film according to the present embodiment may contain other resins other than the poly(3-hydroxyalkanoate)-based resin (A) and the polylactic acid-based resin (B) within the scope of the invention. Examples of such other resins include aliphatic polyester-based resins such as polybutylene succinate adipate, polybutylene succinate, and polycaprolactone, and aliphatic aromatic polyester-based resins such as polybutylene adipate terephthalate, polybutylene sebate terephthalate, and polybutylene azelate terephthalate. Only one type of other resin may be contained, or two or more types may be contained.

[0068] The content of the other resin is not particularly limited, but is preferably 100 parts by weight or less, more preferably 50 parts by weight or less, and even more preferably 30 parts by weight or less, relative to 100 parts by weight of the total of the poly(3-hydroxyalkanoate) resin (A) and the polylactic acid resin (B). It may be 10 parts by weight or less, 5 parts by weight or less, or 1 part by weight or less. The lower limit of the content of the other resin is not particularly limited, and may be 0 parts by weight or more.

[0069] The film according to the present embodiment may contain additives that can be used together with the poly(3-hydroxyalkanoate) resin (A) and the polylactic acid resin (B) within a range that does not impair the effects of the invention. Examples of such additives include colorants such as pigments and dyes, odor absorbents such as activated carbon and zeolite, fragrances such as vanillin and dextrin, fillers, plasticizers, antioxidants, weather resistance improvers, ultraviolet absorbers, lubricants, release agents, water repellents, antibacterial agents, and sliding improvers. Only one type of additive may be contained, or two or more types may be contained. The content of these additives can be appropriately set by a person skilled in the art depending on the purpose of use. The lubricants, fillers, and plasticizers are described in more detail below.

[0070] (lubricant) The film according to the present embodiment may contain a lubricant. Examples of the lubricant include behenamide, oleamide, erucamide, stearamide, palmitamide, N-stearylbehenamide, N-stearylerucamide, ethylenebisstearamide, ethylenebisoleamide, ethylenebiserucamide, ethylenebislauramide, ethylenebiscapricamide, p-phenylenebisstearamide, and polycondensates of ethylenediamine, stearic acid, and sebacic acid. Among them, behenamide or erucamide is preferred because of its particularly excellent lubricant effect on the poly(3-hydroxyalkanoate) resin (A). One or more types of lubricants may be used, and the ratio of use may be appropriately adjusted depending on the purpose.

[0071] When a lubricant is used, the amount thereof is not particularly limited, but is preferably 0.01 to 5 parts by weight, more preferably 0.05 to 3 parts by weight, and even more preferably 0.1 to 1.5 parts by weight, relative to 100 parts by weight in total of the poly(3-hydroxyalkanoate) resin (A) and the polylactic acid resin (B). The film according to the present embodiment preferably contains a lubricant, but does not necessarily need to contain one.

[0072] (filling material) The film according to the present embodiment may contain a filler. By containing a filler, a stretched film with higher strength can be obtained. The filler may be either an inorganic filler or an organic filler, or both may be used in combination. The inorganic filler is not particularly limited, and examples thereof include silicates, carbonates, sulfates, phosphates, oxides, hydroxides, nitrides, and carbon black. Only one type of inorganic filler may be used, or two or more types may be used in combination.

[0073] When the filler is used, the content is not particularly limited, but is preferably 1 to 100 parts by weight, more preferably 3 to 80 parts by weight, even more preferably 5 to 70 parts by weight, and even more preferably 10 to 60 parts by weight, per 100 parts by weight of the total of the poly(3-hydroxyalkanoate)-based resin (A) and the polylactic acid-based resin (B). However, the film according to the present embodiment may not substantially contain a filler. "Substantially no filler is blended" means that the amount of filler blended is less than 1 part by weight per 100 parts by weight of the total of the resin (A) and the resin (B). It may be less than 0.1 part by weight.

[0074] (Plasticizer) The film according to the present embodiment may contain a plasticizer. Examples of the plasticizer include glycerin ester compounds, citrate compounds, sebacic acid ester compounds, adipate compounds, polyether ester compounds, benzoic acid ester compounds, phthalic acid ester compounds, isosorbide ester compounds, polycaprolactone compounds, and dibasic acid ester compounds. Among them, glycerin ester compounds, citrate compounds, sebacic acid ester compounds, and dibasic acid ester compounds are preferred because of their particularly excellent plasticizing effect on the poly(3-hydroxyalkanoate) resin (A). Examples of the glycerin ester compounds include glycerin diacetomonolaurate and the like. Examples of the citrate compounds include acetyl tributyl citrate and the like. Examples of the sebacic acid ester compounds include dibutyl sebacate and the like. Examples of the dibasic acid ester compounds include benzyl methyl diethylene glycol adipate and the like. One type of plasticizer may be used, or two or more types may be used, and the ratio of use can be appropriately adjusted depending on the purpose.

[0075] When a plasticizer is used, the amount used is not particularly limited, but is preferably 1 to 20 parts by weight, more preferably 2 to 15 parts by weight, and even more preferably 3 to 10 parts by weight, per 100 parts by weight of the total of the poly(3-hydroxyalkanoate) resin (A) and the polylactic acid resin (B). However, the film according to the present embodiment may be substantially free of plasticizer. Substantially free of plasticizer means that the amount of plasticizer is less than 1 part by weight per 100 parts by weight of the total of the resin (A) and the resin (B). It may be less than 0.1 part by weight.

[0076] [film] The film according to the present embodiment may be an unstretched film that has not been subjected to a stretching treatment, or may be a stretched film that has been stretched in the MD direction and / or TD direction after film formation. The term "film" in the present application may include both an unstretched film and a stretched film. From the viewpoint of strength, a stretched film is preferable.

[0077] The thickness of the film according to this embodiment (particularly the stretched film) is preferably 10 to 200 μm, more preferably 15 to 150 μm, and even more preferably 20 to 100 μm, from the viewpoints of uniform thickness, appearance, strength, lightness, and the like of the film.

[0078] In addition, the film according to the present embodiment is preferably an industrially produced long film, and more preferably a strip-shaped film wound into a roll. The length of such a film is not particularly limited, but may be, for example, 50 m or more, or 100 m or more. In the present embodiment, such a long film can be continuously and stably produced.

[0079] According to a preferred embodiment, the stretched film according to the present invention can exhibit an elastic modulus of 1500 MPa or more and a breaking strength of 40 MPa or more at least in the MD direction. It may also be a biaxially stretched film exhibiting an elastic modulus of 1500 MPa or more and a breaking strength of 40 MPa or more in both the MD direction and the TD direction. The elastic modulus is preferably 2000 MPa or more, more preferably 2500 MPa or more. The breaking strength is preferably 60 MPa or more, more preferably 70 MPa or more. The elastic modulus and the breaking strength are values ​​measured by a method described in detail in the Examples section.

[0080] [Film manufacturing method] Next, an example of a method for producing the film according to the present embodiment will be described, but the present invention is not limited to the following description. First, a film raw material containing the poly(3-hydroxyalkanoate) resin (A), the polylactic acid resin (B), and, if necessary, other components, is melted.

[0081] The melting method is not particularly limited, but it is preferable to extrude the molten film raw material from a T-die, that is, to carry out an extrusion molding method. By the extrusion molding method, a film with a uniform thickness can be easily produced. In the extrusion molding, a single screw extruder, a twin screw extruder, etc. can be appropriately used.

[0082] The conditions for melting the film raw materials may be any conditions under which the poly(3-hydroxyalkanoate) resin (A) and the polylactic acid resin (B) melt, and the temperature of the molten film raw materials may be, for example, about 140 to 210°C.

[0083] The molten film raw material is then extruded onto a casting roll to form a film. The molten film raw material comes into contact with the casting roll and moves along the surface of the casting roll, whereby it is cooled and solidified. According to this embodiment, since the film raw material does not substantially contain sugar alcohols, it is possible to avoid the problem of contamination of the casting roll surface. In addition, since the polylactic acid-based resin (B) is blended, the film raw material is less likely to stick to the casting roll, so that the production speed can be increased even though the film raw material does not substantially contain sugar alcohols.

[0084] This step may be a step of extruding the molten material onto one or more casting rolls, or a step of opposing a touch roll to a casting roll and sandwiching the molten material extruded onto the casting roll between the touch rolls. In order to bring the molten material into stable contact with the casting roll, an air knife or an air chamber may be used. In order to efficiently cool the opposite side of the contact surface with the casting roll, the casting roll may be placed in a water tank or an air chamber may be used.

[0085] The lower limit of the set temperature of the casting roll is preferably 0° C. or higher, more preferably 10° C. or higher, and even more preferably 15° C. or higher, in order to suppress the adhesion of the poly(3-hydroxyalkanoate) resin (A) and improve the peelability from the casting roll. In addition, the temperature is preferably a temperature higher than the glass transition temperature (Tg) of the poly(3-hydroxyalkanoate) resin (A) + 10° C.

[0086] The upper limit of the temperature set for the cast roll is not particularly limited, but from the viewpoint of promoting solidification of the poly(3-hydroxyalkanoate) resin (A), it is preferably 80° C. or lower, more preferably 60° C. or lower.

[0087] Next, the film cooled on the casting roll is transported while rotating the casting roll, and the film is peeled off from the casting roll, thereby obtaining an unstretched film.

[0088] Next, the obtained film is stretched in the MD direction to obtain a uniaxially stretched film with high strength in the MD direction. The MD direction is also called the machine direction, flow direction, or longitudinal direction. The TD direction, which will be described later, is the direction perpendicular to the MD direction and is also called the perpendicular direction or width direction.

[0089] The stretching process in the MD direction can be carried out continuously from the peeling off from the cast roll in one production line. This process is not particularly limited, but can be carried out, for example, by using a roll longitudinal stretching machine and varying the rotation speed of the rolls that transport the film.

[0090] The stretching step in the MD direction is preferably performed while heating the film. The heating method is not particularly limited, but includes a method of exposing the film to an air flow adjusted to a predetermined temperature, a method of controlling the film temperature by setting a roll to a predetermined temperature, a method of heating the film using an auxiliary heating means such as an IR heater to control the film temperature to a predetermined temperature, and a method of passing the film through an oven adjusted to a predetermined temperature. These methods may be used alone or in combination.

[0091] In the production of the film according to this embodiment, the temperature during stretching in the MD direction is preferably 35°C or higher, more preferably 45°C or higher, and even more preferably 55°C or higher. Since polylactic acid resins usually have a glass transition temperature of around 60°C and are difficult to crystallize when rapidly cooled from a molten state, becoming amorphous, the film according to this embodiment is likely to soften in the above temperature range even if it is below the melting point of the poly(3-hydroxyalkanoate) resin, and good stretching is possible. In addition, the temperature is easy to control and stabilize. Therefore, the film can be stretched continuously and stably, and a long stretched film can be stably produced.

[0092] The upper limit of the temperature during stretching in the MD direction is not particularly limited, but from the viewpoint of avoiding breakage of the film during stretching, it is preferably 110° C. or less, more preferably 100° C. or less, and more preferably 90° C. or less.

[0093] The stretching ratio in the MD direction is not particularly limited, but is preferably 2 times or more. More preferably, it is 2.5 times or more, and further preferably, it is 3 times or more. According to the composition of the film raw material according to the present embodiment, such a high stretching ratio can be realized. The upper limit of the stretching ratio is not particularly limited and may be appropriately determined, but may be, for example, 8 times or less.

[0094] Next, by stretching in the MD direction and then stretching in the TD direction, a biaxially stretched film with high strength in both the MD and TD directions can be obtained. The stretching step in the TD direction can be carried out in one production line, continuously from the stretching step in the MD direction. This step is not particularly limited, but can be carried out, for example, by clamping both ends of the film in the width direction using a transverse stretching machine such as a clip-type tenter and pulling it in the TD direction.

[0095] The stretching step in the TD direction is also preferably performed while heating the film. The heating method is not particularly limited, and may be the same as that described above for the stretching step in the MD direction.

[0096] The temperature during stretching in the TD direction may be the same as the temperature during stretching in the MD direction described above, and is preferably 35 to 110°C, more preferably 45 to 100°C, and more preferably 55 to 90°C.

[0097] The stretching ratio in the TD direction is not particularly limited, but is preferably 2 times or more. More preferably, it is 3 times or more, and further preferably, it is 4 times or more. According to the composition of the film raw material according to the present embodiment, such a high stretching ratio can be realized. The upper limit of the stretching ratio is not particularly limited and may be appropriately determined, but may be, for example, 8 times or less.

[0098] After the MD stretching step or the TD stretching step, it is preferable to carry out a heat setting step in which the stretched film is heated to a temperature at which high-melting crystals grow, thereby increasing the crystallinity of the stretched film, increasing its strength, and stabilizing its physical properties.

[0099] The heating temperature during heat setting is preferably 80 to 150° C., more preferably 90 to 135° C., and most preferably 100 to 130° C. If the heating temperature is 80° C. or higher, the crystallinity of the stretched film increases, and the crystals formed may have a high melting point. If the heating temperature is 150° C. or lower, breakage due to melting of the film can be avoided.

[0100] This heating can be carried out, for example, by stretching in the TD direction using a transverse stretching machine such as a clip-type tenter, and then heating while maintaining the stretched state. At this time, since heat shrinkage occurs in the direction opposite to the stretching direction, it is preferable to relax so as not to break. Relaxation is an operation of returning tension in the direction opposite to the stretching direction, and it is preferable to appropriately adjust the amount of relaxation between 5 and 30%.

[0101] Thereafter, a step of cooling the film may be carried out as appropriate, and then, preferably, a step of winding the stretched film on a winding roll is carried out.

[0102] The film manufacturing method according to the present embodiment is preferably carried out while continuously transporting the film from melt extrusion to the final step. This makes it possible to manufacture the film with good productivity through an industrially simple process. The manufacturing method according to the present embodiment can be carried out while continuously winding up the manufactured film on a winding roll.

[0103] When the film is continuously transported, the transport speed is not particularly limited, but from the viewpoint of film productivity, it is preferably 5 m / min or more before the start of stretching, and from the viewpoint of production stability, it is preferably 50 m / min or less before the start of stretching.

[0104] [Laminate] The film according to the present embodiment may be a resin film composed of an independent single layer, but may also be a laminate in which other layers are laminated on one or both sides of the film. Such a laminate also constitutes one aspect of the present invention. Examples of the other layer include a resin layer, an inorganic layer, a metal layer, a metal oxide layer, a printed layer, etc. These other layers may be laminate layers, coating layers, or vapor deposition layers.

[0105] The resin layer, which is one of the other layers in the laminate, is not particularly limited, but is preferably a layer containing a poly(3-hydroxyalkanoate) resin (C) from the viewpoint of enhancing the biodegradability of the entire laminate. As the poly(3-hydroxyalkanoate) resin (C), those described above for the poly(3-hydroxyalkanoate) resin (A) can be appropriately used, but are not particularly limited. There are also no particular limitations on the components other than the poly(3-hydroxyalkanoate) resin (C), and known components can be appropriately used as additives to the resin layer. This resin layer may function as a heat seal layer.

[0106] [Film Uses] The film according to this embodiment can be suitably used as a packaging film, a heat sealable film, a twist film, and the like.

[0107] The following items enumerate preferred aspects of the present disclosure, but the present invention is not limited to the following items. [Item 1] Contains a poly(3-hydroxyalkanoate) resin (A) and a polylactic acid resin (B), Contains substantially no sugar alcohols, The film, wherein the weight ratio (A / B) of the poly(3-hydroxyalkanoate) resin (A) to the polylactic acid resin (B) is 85 / 15 to 55 / 45. [Item 2] The poly(3-hydroxyalkanoate) resin (A) is A copolymer (A-1) of 3-hydroxybutyrate units and other hydroxyalkanoate units, the content of which is 24 mol % or more, and The film according to item 1, comprising a copolymer (A-2) of 3-hydroxybutyrate units and other hydroxyalkanoate units, the content of which is 1 mol% or more and 9 mol% or less of the other hydroxyalkanoate units. [Item 3] 3. The film according to item 2, wherein the content of the copolymer (A-1) of 3-hydroxybutyrate units and other hydroxyalkanoate units, in which the content of the other hydroxyalkanoate units is 24 mol % or more, is more than 0 wt % and less than 30 wt % based on the total weight of the poly(3-hydroxyalkanoate)-based resin (A) and the polylactic acid-based resin (B). [Item 4] 4. The film according to item 2 or 3, wherein the content of the copolymer (A-2) of 3-hydroxybutyrate units and other hydroxyalkanoate units, in which the content of the other hydroxyalkanoate units is from 1 mol % to 9 mol %, is more than 0 wt % and less than 70 wt % based on the total weight of the poly(3-hydroxyalkanoate)-based resin (A) and the polylactic acid-based resin (B). [Item 5] 5. The film according to any one of items 2 to 4, wherein a weight ratio (A-1 / A-2) of the copolymer (A-1) of 3-hydroxybutyrate units and other hydroxyalkanoate units, in which the content of the other hydroxyalkanoate units is 24 mol % or more, and the copolymer (A-2) of 3-hydroxybutyrate units and other hydroxyalkanoate units, in which the content of the other hydroxyalkanoate units is 1 mol % or more and 9 mol % or less, is 20 / 80 to 30 / 70. [Item 6] 6. The film according to any one of items 2 to 5, wherein the other hydroxyalkanoate units include 3-hydroxyhexanoate units. [Item 7] 7. The film according to any one of items 1 to 6, wherein the film is a stretched film. [Item 8] Item 8. The film according to item 7, wherein the stretched film exhibits an elastic modulus of 1500 MPa or more and a breaking strength of 40 MPa or more, at least in the MD direction. [Item 9] 9. A laminate comprising the film according to any one of items 1 to 8, and a layer containing a poly(3-hydroxyalkanoate) resin (C) laminated on at least one surface of the film. EXAMPLES

[0108] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples in any way.

[0109] In the examples, the following raw materials were used: (Poly(3-hydroxyalkanoate) resin (A)) As the P3HA resin (A), the following poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (P3HB3HH) resins PHBH-1 to PHBH-3 were used, where 3HB below represents a 3-hydroxybutyrate repeating unit, and 3HH represents a 3-hydroxyhexanoate repeating unit. PHBH-1: P3HB3HH (average content ratio 3HB / 3HH = 71.8 / 28.2 (mol% / mol%), weight average molecular weight is 660,000 g / mol) It was produced in accordance with the method described in Example 9 of WO 2019 / 142845. PHBH-2: P3HB3HH (average content ratio 3HB / 3HH = 97.2 / 2.8 (mol% / mol%), weight average molecular weight is 660,000 g / mol) It was produced in accordance with the method described in Example 2 of WO 2019 / 142845. PHBH-3: P3HB3HH (average content ratio 3HB / 3HH = 94 / 6 (mol% / mol%), weight average molecular weight is 600,000 g / mol) It was produced in accordance with the method described in Example 1 of WO 2019 / 142845.

[0110] (Polylactic acid resin (B)) B-1: PLA (LX175 grade, manufactured by Total Corbion PLA, melting point peak temperature is 155℃)

[0111] (Crystal nucleating agent) C-1: Pentaerythritol (Mitsubishi Chemical, NeuRizer P)

[0112] (lubricant) D-1: Behenamide (Nippon Fine Chemicals: BNT-22H)

[0113] In each of the Examples and Comparative Examples, the following evaluations were carried out. [T-die film formability] (Roll contamination) The P3HA resin composition was melted at 165°C in a single-screw extruder with a screw diameter of 20 mm, and taken from a die with a lip width of 250 μm at a cast roll (CR) temperature of 40 to 60°C at the take-up speed shown in Table 1 to obtain a T-die film of the P3HA resin composition. At this time, the T-die film moldability was evaluated according to the following evaluation criteria.

[0114] <Evaluation criteria> ◯: The surface of the cast roll after one hour of continuous operation was visually observed, and the boundary between the film contact area and the non-contact area could not be detected. ×: The surface of the cast roll after one hour of continuous operation was visually observed, and the boundary between the film contact area and the non-contact area could be detected.

[0115] [Film stretchability] A film was produced using the resin pellets with a T-die, and continuously stretched 3 times in the MD direction (flow direction of T-die film production) in a temperature range of 60°C to 70°C using a roll centrifuge, and the stretchable region (stretch ratio) was evaluated according to the following evaluation criteria. In addition, the film stretched in the MD direction was fixed at both ends in the MD direction and stretched 5 times in the TD direction (perpendicular to the MD direction) at a temperature range of 70°C to 80°C, and the stretchable region (stretching ratio) was evaluated according to the following evaluation criteria.

[0116] <Evaluation criteria> ◯: The film was obtained without breaking during stretching, and no stretching unevenness (uneven stretching portions such as film thickness) was visually observed in the obtained film. △: The film was obtained without breaking during stretching, and the obtained film had no visible stretching unevenness (uneven stretching areas such as film thickness). However, the thickness fluctuation was slightly larger than that of ◯. However, in TD stretching, the film was able to be stretched without unevenness. ×: The film broke during stretching, or stretching unevenness (uneven stretching portions in the film thickness, etc.) was visually observed in the obtained film.

[0117] [Film properties] <Film elastic modulus, breaking strength, and breaking elongation> After storing a 20 μm-thick film for one week at 23°C and 50% humidity, ten dumbbells (small test pieces, size 2(1 / 3)) were punched out in the MD and / or TD directions according to JIS K7113, and the elastic modulus, breaking strength and breaking elongation were measured and calculated five times at a test speed of 100 mm / min using a tensile testing machine (Shimadzu Corporation, "AUTOGRAPH AG2000A"), and the average values ​​are shown in Table 1 as the elastic modulus, breaking strength and breaking elongation.

[0118] <Film tear strength> After storing the film for one week under an atmosphere of 23°C and 50% humidity, the tear strength was measured using the Elmendorf tear method based on JIS K-1281. The measurement was carried out five times, and the average value was recorded as the tear strength in Table 1.

[0119] [Biodegradable] The degree of biodegradation was calculated as the ratio of biological oxygen demand (BOD) to theoretical oxygen demand (ThOD) and evaluated according to the following evaluation criteria. Specifically, with regard to home compostability, biodegradation tests were conducted at 28±2°C in accordance with ISO 14855-1 (28±2°C) and JIS K 6953-1, and the biodegradability was calculated as the ratio of the amount of carbon dioxide generated to the theoretical amount of carbon dioxide generated.

[0120] <Evaluation criteria> XXX:BOD75% or more 〇〇: BOD 70% or more but less than 75% ○: BOD 65% or more but less than 70% △: Less than 65%

[0121] Example 1 (Method of producing resin composition) 0.5 parts by weight of D-1 was dry-blended as a lubricant with 30 parts by weight of poly(3-hydroxyalkanoate) resin PHBH-1, 30 parts by weight of PHBH-2, and 40 parts by weight of PHBH-3. The resulting resin material was charged into a hopper of a φ26 mm co-rotating twin-screw extruder with cylinder and die temperatures set at 150° C., melt-kneaded, and extruded from the die in the form of strands, which were passed through a water tank filled with hot water at 45° C. to solidify the strands, and cut with a pelletizer to obtain resin pellets P-1.

[0122] (Manufacture of biaxially stretched film in MD and TD directions) Furthermore, the resin pellets P-1 and B-1 were put into a single-screw extruder so that the weight ratio was 80:20, and extruded into a film shape with a T-die. The formed film was cooled with a cooling roll set at a temperature of 50 ° C., then taken up with a take-up roll, and continuously stretched in the MD direction by 3 times at 60 to 70 ° C. with a roll longitudinal stretching machine, and then continuously stretched in the TD direction at a stretching temperature of 70 to 80 ° C. with a clip-type tenter transverse stretching machine so that the stretching ratio was 5 times, and then heated to 130 ° C. while relaxing the stretching by 15% to heat set. The film after biaxial stretching was cooled to 50 ° C., and the width direction end was slit to obtain a biaxially stretched film with a width of 1200 mm and a thickness of 20 μm. The above process was carried out continuously.

[0123] After one hour of continuous operation from the start of T-die film production, roll contamination was evaluated. In addition, the film was observed after MD stretching and after TD stretching to evaluate the stretchability of the film. In addition, the elastic modulus, breaking strength, breaking elongation, tear strength, and biodegradability of the obtained stretched film were evaluated, and the evaluation results are shown in Table 1.

[0124] (Examples 2 to 5) Resin pellets P-2 to P-5 were produced in the same manner as in Example 1, except that the composition was changed as shown in Table 1. In addition, a film was produced in the same manner as in Example 1, and the roll contamination property, film stretchability, elastic modulus of the stretched film, tensile strength, breaking strength, breaking elongation, tear strength, and biodegradability were evaluated. The evaluation results are shown in Table 1. In Example 1, the maximum molding speed at which film molding could be performed without the resin material sticking to the casting roll was 7 m / min, but in Examples 2 to 5, film molding could be performed without problems even when the molding speed was increased to 18.5 m / min.

[0125] (Comparative Examples 1 and 2) Resin pellets P-6 and 7 were produced in the same manner as in Example 1, except that the composition was changed as shown in Table 1. Films were produced in the same manner as in Example 1, and the roll contamination property, film stretchability, elastic modulus, tensile strength, breaking strength, breaking elongation, tear strength, and biodegradability of the stretched film were evaluated. The evaluation results are shown in Table 1.

[0126] Comparative Example 3 Resin pellets P-8 were produced in the same manner as in Example 1, except that the composition was changed as shown in Table 1. An attempt was made to produce a film in the same manner as in Example 1. Although the film contamination resistance was good, the molten film did not solidify on the casting roll, and even when the molding speed was less than 1 m / min, the film stuck to the casting roll and could not be peeled off, so that a film could not be obtained.

[0127] [Table 1]

[0128] As shown in Table 1, in Examples 1 to 5 in which a specific amount of polylactic acid resin (B) was used without adding sugar alcohols, no roll contamination was observed and films could be molded with good productivity. In particular, Examples 2 to 5 had good productivity. On the other hand, in Comparative Examples 1 and 2, in which both polylactic acid resin (B) and sugar alcohols (pentaerythritol) were blended, film productivity was good, but roll contamination was observed. In Comparative Example 3, in which neither polylactic acid resin (B) nor sugar alcohols were blended, roll contamination did not occur, but the film material was prone to sticking to the casting roll, making it impossible to produce a film.

Claims

1. Contains a poly(3-hydroxyalkanoate)-based resin (A) and a polylactic acid-based resin (B), Contains substantially no sugar alcohols, The weight ratio (A / B) of the poly(3-hydroxyalkanoate)-based resin (A) to the polylactic acid-based resin (B) is 85 / 15 to 55 / 45.

2. The poly(3-hydroxyalkanoate)-based resin (A) is A copolymer (A-1) of 3-hydroxybutyrate units and other hydroxyalkanoate units, the content of which is 24 mol % or more of the other hydroxyalkanoate units; and The film according to claim 1, comprising a copolymer (A-2) of 3-hydroxybutyrate units and other hydroxyalkanoate units, the content of which is from 1 mol % to 9 mol %.

3. 3. The film according to claim 2, wherein the content of the copolymer (A-1) of 3-hydroxybutyrate units and other hydroxyalkanoate units, in which the content of the other hydroxyalkanoate units is 24 mol % or more, is more than 0 wt % and less than 30 wt % based on the total weight of the poly(3-hydroxyalkanoate)-based resin (A) and the polylactic acid-based resin (B).

4. 4. The film according to claim 2 or 3, wherein the content of the copolymer (A-2) of 3-hydroxybutyrate units and other hydroxyalkanoate units, in which the content of the other hydroxyalkanoate units is from 1 mol % to 9 mol %, is more than 0 wt % and less than 70 wt % based on the total weight of the poly(3-hydroxyalkanoate)-based resin (A) and the polylactic acid-based resin (B).

5. The film according to claim 2 or 3, wherein the weight ratio (A-1 / A-2) of the copolymer (A-1) of 3-hydroxybutyrate units and other hydroxyalkanoate units, in which the content of the other hydroxyalkanoate units is 24 mol% or more, and the copolymer (A-2) of 3-hydroxybutyrate units and other hydroxyalkanoate units, in which the content of the other hydroxyalkanoate units is 1 mol% or more and 9 mol% or less, is 20 / 80 to 30 / 70.

6. The film of claim 2 or 3, wherein the other hydroxyalkanoate units include 3-hydroxyhexanoate units.

7. The film of claim 1 or 2, wherein the film is a stretched film.

8. The film according to claim 7, wherein the stretched film exhibits an elastic modulus of 1500 MPa or more and a breaking strength of 40 MPa or more at least in the MD direction.

9. A laminate comprising the film according to claim 1 or 2, and a layer containing a poly(3-hydroxyalkanoate)-based resin (C) laminated on at least one surface of the film.

Citation Information

Patent Citations

  • Biodegradable resin composition

    WO2008099586A1

  • Polyester resin composition and molded body containing this resin composition

    WO2014020838A1

Cited By

  • Multilayer film and method for producing same

    WO2026191635A1